Chicagoland Detective Agency. The big flush 4 - Robbins, Trina (Chicagoland Detective Agency, 2012)
Ousted from Stepford Prep, Megan attends a prospective students event with friend Raf and talking dog Bradley at Pine Lake Academy, where Raf is possessed by the spirit of a teenaged girl from the 1910s after drinking from an old water fountain.